The influence of Quantum Teaching learning Model on Science Learning Outcomes - Larasati, Gustina; Baadilla , Irwan (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This study aims to determine the effect of the quantum teaching-learning model on the learning outcomes of science students in Grade V of SDN Balekambang 01 Pagi Jakarta academic year 2022-2023. Quantum teaching learning Model is a teaching that fosters a pleasant learning atmosphere by promoting curiosity and adding student experience, a type of quantitative research in the form of proper experimental design pretest–posttest control grub design. Samples were taken randomly from as many as 32 practical and 32 control class students. Based on the T-test, it is known that with a significance level of a = 0.05 with sig. (2-tailed) = 0.039 so that H1 is accepted and Ho rejected. It can be concluded that the quantum teaching-learning model significantly influences the learning outcomes of science students in Grade V of SDN Balekambang 01 Pagi.